Manfaat Adiponektin Dan Leptin Dalam Memantau Efek Latihan Fisik Terhadap Fungsi Adiposa Penderita Sindrom Metabolik - Nani Cahyani Sudarsono; Bunga Listia Paramita; Diczen Diczen; Dimas Nugroho; Meisya Shabrina (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: The Prevalence of metabolic syndrome (MetS) in Indonesia is increasing, with the highest age in the 45 – 54 years old, and high mortality and morbidity rates complications and cost. Biomarkers such as adiponectin, leptin, and their ratios may be useful in monitoring and quantifying patient's body fat tissue function improvement after exercise training. This study aims to determine adiponectin, leptin, and their ratios benefits in monitoring physical exercise effects on adipose tissue function in pre-elderly (45-59 years old) and elderly (greater than 60 years old) patients with MetS.Methods: Literature review through hand searching and pubmed database related to the benefits of leptin and adiponectin test in monitoring physical exercise effect on adipose function in the pre-elderly and/or elderly population with MetS.Results: Physical exercise significantly increased adiponectin levels (mean difference (MD): 0.42 µg/mL; 95% CI 0.23, 0.60, p less than 0.0001), and reduced leptin levels (MD: -1.89 ng /ml; 95% CI, -2.64, -1.14, p less than 0.0001). High-intensity aerobic exercise can even reduce serum leptin levels by 6.29 ng/ml (p less than 0.001), and increase serum adiponectin levels by 0.74 μg/ml (p = 0.04). This significant change mainly occurs in men with a Body Mass Index (BMI) of 30 kg/m2 and 25.0-29. 9 kg/m2.Conclusion: Adiponectin/leptin ratio examination has potential future benefits in MetS management as an evaluation physiological biomarkers related to exercise interventions. There are only a few capable laboratories, and expensive cost, so that its current implementation is mostly devoted to research. Adopting a healthy lifestyle, balanced nutrition, physical activity habits and regular physical exercise are still the best suggestions for preventing MetS.